Analisis Efektivitas Program Corporate Social Responsibility (CSR) terhadap Citra Perusahaan di Sektor Keuangan - Dadang Irawan; Mohammad Chaidir; Benardi Benardi (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyze the effectiveness of Corporate Social Responsibility (CSR) programs in enhancing corporate image in the financial sector and to identify key factors influencing their success. CSR has become a crucial strategy for companies to build positive relationships with society and establish a strong reputation. Through a literature review approach, this research evaluates how well-structured and integrated CSR implementation with business strategies can strengthen corporate image. The findings indicate that the success of CSR depends on its integration with core business operations, active stakeholder engagement, transparency, and accountability in reporting. Additionally, CSR programs tailored to local community needs can create significant social impact while supporting the company’s business sustainability. This study provides strategic recommendations for improving CSR implementation effectiveness, including the importance of collaboration with local communities and transparent reporting practices. Consequently, CSR contributes to corporate reputation and creates long-term value for society and other stakeholders.